Pengaruh Media Pazar terhadap Pemahaman Konsep dan Karakter Mandiri Materi Peredaran Darah Manusia pada Siswa Kelas V SD - Gabby Andriana Puspitasari; Surayanah Surayanah; Surayana Surayana (FONDATIA, 2026)
This study was motivated by students’ low conceptual understanding and independent character in science learning, particularly on the topic of human blood circulation in fifth grade of elementary school. The abstract nature of the material, along with still-conventional learning practices, causes students to experience difficulties in understanding concepts in depth and to demonstrate low learning independence. This study aims to analyze the effect of PAZAR media (Augmented Reality-based Puzzle) on students’ conceptual understanding and independent character. This study employed a quasi-experimental method with a pretest-posttest control group design in the experimental class and the control class. Data were collected through a conceptual understanding test and an independent character questionnaire, and were then analyzed using a paired sample t-test and MANOVA after fulfilling the prerequisite tests of normality and homogeneity. The results showed that PAZAR media had a significant effect on students’ conceptual understanding (0.000 < 0.05), students’ independent character (0.002 < 0.05), as well as simultaneously on both based on the MANOVA test (0.000 < 0.05). The conclusion of this study confirms that PAZAR media has an effect on improving students’ conceptual understanding and independent character on the topic of human blood circulation. These findings contribute to the development of innovative learning media that support the strengthening of students’ cognitive and character aspects in science learning in elementary school.